Perang Jepang Rusia 1904-1905: Konflik Perebutan Hegemoni di Wilayah Asia Timur - Kusuma, Ananta Dharma (Lambung Mangkurat University, 2023)
In the history of international conflicts, the common cause that becomes the trigger is the expansion of hegemony. One of the conflicts recorded due to the expansion of the hegemony area occurred between Japan and Russia, which began in the second half of the 19th century and continued until the beginning of the 20th century. The conflict heated up and succeeded in triggering an open war between the two countries. The war ended with the signing of the Portsmouth agreement on 5 September 1905, with Japan as the victor. The impact of the war was not only felt by the two countries but on a global scale. This paper focuses on the first issue regarding the background of the 1904-1905 Japan-Russia war, the second regarding the tactical steps of Japan's victory in the war with Russia 1904-1905, and the third regarding the impact arising from the existence of the Japan-Russia war. This paper uses the historical method, which consists of topic selection, heuristics, interpretation and historiography. This article aims to provide information regarding the chronology of the conflict between Japan and Russia, which led to the great war in 1904-1905.